Gonad-Specific Transcriptomes Reveal Differential Expression of Gene and miRNA Between Male and Female of the Discus Fish (Symphysodon aequifasciatus) - Fu, Yuanshuai; Xu, Zhe; Wen, Bin; Gao, Jianzhong; Chen, Zaizhong (Frontiers in Physiology, 2020)
The discus fish (Symphysodon aequifasciatus) is an ornamental fish that is well-known around the world. In artificial reproduction, they must be matched by one male and one female, whereas phenotype investigation indicated that there are no significant differences in appearance between males and females, which causes great difficulties in the mating during artificial reproduction. So, it is of great importance to establish artificial sex identification methods for the discus fish. The molecular mechanism of the sexual dimorphism of the discus fish was previously unknown. In this study, we constructed six cDNA libraries from three adult testes and three adult ovaries and performed RNA sequencing for identifying sex-biased candidate genes and microRNAs (miRNAs). A total of 50,082 non-redundant genes (unigenes) were identified, of which 18,570 unigenes were significantly overexpressed in testes, and 11,182 unigenes were significantly overexpressed in ovaries. A total of 551 miRNAs were identified, of which 47 miRNAs were differentially expressed between testes and ovaries. Eight differentially expressed unigenes, seven differentially expressed miRNAs and one non-differential miRNA were validated by quantitative real-time polymerase chain reaction. Twenty-four of these differentially expressed miRNAs and their 15 predicted target genes constituted 41 miRNA–mRNA interaction pairs, and some of vital sex-related metabolic pathways were also identified. These results revealed these differentially expressed genes and miRNAs between ovary and testis might be involved in regulating gonadal development, sex determination, gametogenesis, and physiological function maintenance, and there are complex regulatory networks between genes and miRNAs. It can help us understand the molecular mechanism of the sexual dimorphism and obtain a high-efficiency sex identification method in the artificial reproduction process of the discus fish.